Self-adhesive laminate and method for producing same

By integrating metal-containing oxidized cellulose nanofibers into self-adsorbing foam sheets and employing a breathable substrate with optimized properties, the self-adsorbing laminate achieves superior deodorizing performance and manufacturing efficiency.

JP7647153B2Active Publication Date: 2025-03-18ZEON CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021025626
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-19
Publication Date
2025-03-18
Estimated Expiration
2041-02-19

AI Technical Summary

Technical Problem

Conventional self-adsorbing laminates using modified cellulose nanofibers are not sufficiently deodorizing, and when using a breathable substrate, the foaming composition can pass through, causing manufacturing issues and reduced yield.

Method used

Incorporating metal-containing oxidized cellulose nanofibers with metals other than sodium into the self-adsorbing foam sheet and using a breathable substrate with a specific basis weight and ventilation rate to enhance deodorizing properties while preventing substrate permeation.

Benefits of technology

The solution results in a self-adsorbing laminate with improved deodorizing capabilities and efficient production, as the metal-containing nanofibers enhance adsorption and the substrate configuration prevents foaming composition permeation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647153000001
    Figure 0007647153000001
Patent Text Reader

Abstract

To provide a self-adsorption laminate which is excellent in deodorizing properties and can be efficiently manufactured.SOLUTION: The self-adsorption laminate includes a substrate and a self-adsorption foam sheet. The self-adsorption foam sheet contains a polymer and metal-containing oxidized cellulose nanofibers containing a metal other than sodium in the form of a salt. The substrate has an air permeability of more than 0 cm3 / cm2 / s and a basis weight of 40 g / m2 or more. The polymer preferably contains an acrylate monomer unit and / or a methacrylate monomer unit.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a self-adhesive laminate and a method for producing a self-adhesive laminate. [Background technology]

[0002] Conventionally, a sheet-like member having self-adhesive properties, that is, a self-adhesive foam sheet (hereinafter, sometimes simply referred to as a "foam sheet"), made of a foam material having a large number of fine pores, has been used as an adhesive sheet to be attached to a smooth adherend such as a window glass. The adhesive mode of the self-adhesive foam sheet is not glue adhesion, but adhesion to the adherend utilizing the fine pores. Therefore, the self-adhesive foam sheet is easier to reattach than the conventional adhesive sheet using glue adhesion, and is suitably used for applications such as wallpaper, posters, and stickers. When used for these applications, the self-adhesive foam sheet is usually used in the form of a self-adhesive laminate (hereinafter, sometimes simply referred to as a "laminate sheet") laminated with a substrate. This self-adhesive laminate is produced, for example, by forming a foam composition obtained by foaming a composition for self-adhesive foam sheets containing a polymer into a sheet on a substrate. The self-adhesive laminate can be advantageously used for the above-mentioned applications by applying decoration such as printing to the surface on the substrate side.

[0003] In recent years, the addition of modified cellulose nanofibers to resin foams has been considered for the purpose of imparting strength and the ability to adsorb odorous gases, etc. For example, Patent Document 1 describes that a foam with excellent strength and the ability to adsorb odors such as ammonia can be obtained by foaming a resin foam composition containing cellulose nanofibers having sodium salt-type or acid-type carboxyl groups introduced onto their surfaces and a resin emulsion. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2013 / 146847 Summary of the Invention [Problem to be solved by the invention]

[0005] However, according to the inventors' investigations, conventional self-adhesive laminates using self-adhesive foam sheets containing modified cellulose nanofibers having sodium salt-type or acid-type carboxyl groups introduced onto their surfaces did not have sufficient deodorizing properties.

[0006] In response to these problems, the present inventors came up with a new idea of ​​improving the deodorizing properties of the self-adhesive foam sheet itself by using metal-containing oxidized cellulose nanofibers that contain a metal other than sodium in the form of a salt as the cellulose nanofiber, and of using a breathable substrate as the base material to make it easier for gases containing odorous substances to come into contact with the self-adhesive foam sheet, thereby improving the deodorizing properties of the self-adhesive laminate.

[0007] However, when a breathable substrate is used, when a self-adhesive laminate is produced by foaming a composition for a self-adhesive foam sheet to form a foam composition into a sheet on the substrate, the foam composition may permeate the substrate, causing contamination of the production equipment and reducing yields.

[0008] SUMMARY OF THE PRESENT EMBODIMENTS Accordingly, an object of the present invention is to provide a self-adhesive laminate which has excellent deodorizing properties and can be efficiently produced. [Means for solving the problem]

[0009] The present inventors have conducted extensive research with the aim of solving the above problems, and as a result, have newly discovered that the deodorizing properties of a self-adhesive laminate can be improved by incorporating metal-containing oxidized cellulose nanofibers, which contain a metal other than sodium in the form of a salt, into a self-adhesive foam sheet and using a breathable substrate, and that a self-adhesive laminate can be efficiently manufactured by setting the basis weight of the breathable substrate to a predetermined value or more, thereby completing the present invention.

[0010] That is, the present invention has an object to advantageously solve the above-mentioned problems, and the self-adhesive laminate of the present invention comprises a substrate and a self-adhesive foam sheet, the self-adhesive foam sheet comprises a polymer and a metal-containing oxidized cellulose nanofiber containing a metal other than sodium in the form of a salt, and the substrate has an air permeability of 0 cm 3 / cm 2 / sec and the basis weight is 40 g / m 2 In this way, when the self-adsorbing foam sheet contains metal-containing oxidized cellulose nanofibers that contain a metal other than sodium in the form of a salt, and a breathable substrate is used, a self-adsorbing laminate with excellent deodorizing properties can be obtained. In addition, when the basis weight of the substrate is 40 g / m 2 In this way, the material used to form the self-adhesive foam sheet can be prevented from permeating through the substrate, and the self-adhesive laminate can be efficiently produced. In the present invention, the "breathability" and "basis weight" of the substrate can be measured by the method described in the Examples.

[0011] Here, in the self-adhesive laminate of the present invention, the polymer preferably contains a (meth)acrylate monomer unit. A polymer containing a (meth)acrylate monomer unit has excellent flexibility and can impart good adsorption properties to the foam sheet. In the present invention, the phrase "containing a monomer unit" means that "a polymer obtained by using the monomer contains a repeating unit derived from the monomer." In addition, in the present invention, "(meth)acrylate" means acrylate and / or methacrylate.

[0012] In the self-adhesive laminate of the present invention, the metal-containing oxidized cellulose nanofibers preferably have a number average fiber diameter of 100 nm or less. Metal-containing oxidized cellulose nanofibers having a number average fiber diameter of 100 nm or less have excellent dispersibility, and even when incorporated in a small amount, can impart good deodorizing properties to the foam sheet. In the present invention, the "number average fiber diameter" of the metallized oxidized cellulose nanofibers can be determined by measuring the fiber diameters of five or more metallized oxidized cellulose nanofibers using an atomic force microscope and calculating the number average of the measured fiber diameters.

[0013] Furthermore, in the self-adhesive laminate of the present invention, it is preferable that the metal-containing oxidized cellulose nanofiber is a metal-containing carboxylated cellulose nanofiber. The metal-containing carboxylated cellulose nanofiber has excellent dispersibility and can impart good deodorizing properties to the foam sheet even when the amount of the metal-containing carboxylated cellulose nanofiber is small.

[0014] In the self-adhesive laminate of the present invention, the metal other than sodium is preferably at least one selected from the group consisting of silver, zinc, and copper. Metal-containing oxidized cellulose nanofibers containing at least one selected from the group consisting of silver, zinc, and copper have excellent deodorizing properties and can impart good deodorizing properties to the foam sheet.

[0015] In the self-adhesive laminate of the present invention, the substrate preferably contains PET fibers. By using a substrate containing PET (polyethylene terephthalate) fibers, the deodorizing property, strength, and heat resistance of the self-adhesive laminate can be simultaneously achieved at high levels.

[0016] The present invention also aims to advantageously solve the above-mentioned problems, and a method for producing a self-adhesive laminate of the present invention includes a step of foaming a composition for a self-adhesive foam sheet, the composition comprising a polymer and a metal-containing oxidized cellulose nanofiber containing a metal other than sodium in the form of a salt, to obtain a foam composition, and a step of forming the foam composition into a sheet on a substrate, the substrate being a material having an air permeability of 0 cm. 3 / cm 2 / sec and the basis weight is 40 g / m 2In this way, when metal-containing oxidized cellulose nanofibers containing a metal other than sodium in the form of a salt are contained in a composition for a self-adhesive foam sheet and a substrate having air permeability is used, a self-adhesive laminate having excellent deodorizing properties can be obtained. 2 If the above is done, the foaming composition is prevented from permeating the substrate when the foaming composition is molded into a sheet on the substrate, and the self-adhesive laminate can be efficiently produced. Effect of the Invention

[0017] According to the present invention, it is possible to provide a self-adhesive laminate which has excellent deodorizing properties and can be efficiently produced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, an embodiment of the present invention will be described in detail. Here, the self-adhesive laminate of the present invention is used by being attached to an adherend indoors or outdoors, and can be produced, for example, by the method for producing a self-adhesive laminate of the present invention.

[0019] (Self-adhesive laminate) The self-adhesive laminate of the present invention comprises a foam layer made of a self-adhesive foam sheet, and a substrate as a support layer supporting the foam layer. The self-adhesive laminate of the present invention requires that the foam sheet contains a polymer and a metal-containing oxidized cellulose nanofiber containing a metal other than sodium in the form of a salt. The self-adhesive laminate of the present invention further requires that the substrate has an air permeability of 0 cm 3 / cm 2 / sec and the basis weight is 40 g / m 2 It is necessary that the above is true. The foam sheet may be formed directly on the substrate, or may be formed on the substrate via any layer, but from the viewpoint of enhancing the deodorizing properties of the self-adhesive laminate, it is preferable that the foam sheet is formed directly on the substrate. Also, the self-adhesive laminate of the present invention may have foam sheets on both sides of the substrate.

[0020] The foam sheet of the self-adhesive laminate of the present invention contains metal-containing oxidized cellulose nanofibers that contain a metal other than sodium in the form of a salt, and therefore has excellent strength and can exhibit high deodorizing properties. 3 / cm 2 The substrate of the self-adhesive laminate of the present invention has a basis weight of more than 40 g / m2, and the gas containing odorous substances can easily permeate the substrate and come into contact with the foam sheet, so that the substrate exhibits excellent deodorizing properties compared to the substrate that does not have air permeability. 2 As described above, the material used to form the foamed sheet is prevented from permeating through the substrate, and the self-adhesive laminate can be efficiently produced while preventing contamination of the production equipment and a decrease in yield. The odors that can be deodorized by the self-adhesive laminate of the present invention are not particularly limited, and examples thereof include ammonia odor, methyl mercaptan odor, and hydrogen sulfide odor.

[0021] <Self-adhesive foam sheet> The self-adhesive foam sheet has a large number of fine pores, and the self-adhesive laminate is usually attached to an adherend by adsorbing the self-adhesive foam sheet to the adherend. The self-adhesive foam sheet contains a polymer and a metal-containing oxidized cellulose nanofiber containing a metal other than sodium in the form of a salt, and optionally further contains other additives.

[0022] [Polymer] The polymer forms the resin matrix in the foam sheet.

[0023] The polymer may be any polymer capable of forming a foamed sheet. Specifically, the polymer may include, but is not limited to, at least one monomer unit selected from the group consisting of (meth)acrylate monomer units, unsaturated carboxylic acid monomer units, vinyl cyanide monomer units, and alkenyl aromatic monomer units. Among these, it is preferable that the polymer contains a (meth)acrylate monomer unit, because this provides flexibility to the foamed sheet and enables the foamed sheet to exhibit good adsorptive power (self-adhesive power). In addition, the polymer may contain monomer units other than (meth)acrylate monomer units, unsaturated carboxylic acid monomer units, vinyl cyanide monomer units, and alkenyl aromatic monomer units (hereinafter referred to as "other monomer units"). The polymer may have a crosslinked structure formed within and / or between molecules using a crosslinking agent or a crosslinkable monomer unit.

[0024] The (meth)acrylate monomer unit is a repeating unit derived from a (meth)acrylate monomer. The (meth)acrylate monomer is not particularly limited, but examples thereof include (meth)acrylic acid alkyl ester monomers such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-heptyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and n-dodecyl (meth)acrylate; (meth)acrylic acid alkoxy alkyl ester monomers such as 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, and ethoxymethyl (meth)acrylate; and the like. The (meth)acrylate monomers may be used alone or in combination of two or more. In the present invention, "(meth)acrylic" means acrylic and / or methacrylic.

[0025] Here, as the (meth)acrylate monomer, from the viewpoint of further increasing the flexibility of the foamed sheet and further ensuring the self-adhesive strength of the laminated sheet, a (meth)acrylic acid alkyl ester monomer is preferred, and a (meth)acrylic acid alkyl ester monomer having 1 to 14 carbon atoms in the alkyl group bonded to a non-carbonyl oxygen atom (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, n-heptyl acrylate, n-hexyl acrylate, n-octyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, n-octyl methacrylate, n-dodecyl methacrylate, etc.) is more preferred. Among them, from the viewpoint of self-adhesive strength and cost, n-butyl acrylate, ethyl acrylate, and 2-ethylhexyl acrylate are preferred.

[0026] The proportion of the (meth)acrylate monomer units in the polymer is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 85% by mass or more, and preferably 99% by mass or less, more preferably 95% by mass or less, and even more preferably 92% by mass or less, based on the total repeating units (total monomer units) contained in the polymer being 100% by mass. If the proportion of the (meth)acrylate monomer units in the polymer is 60% by mass or more, the self-adhesive strength of the foamed sheet can be sufficiently ensured. On the other hand, if the proportion of the (meth)acrylate monomer units in the polymer is 99% by mass or less, the self-adhesive strength of the foamed sheet does not increase excessively. Therefore, the resin residue on the adherend of the self-adhesive laminate having the foamed sheet can be suppressed.

[0027] The unsaturated carboxylic acid monomer unit is a repeating unit derived from an unsaturated carboxylic acid monomer. Specific examples of the unsaturated carboxylic acid monomer include α,β-ethylenically unsaturated monocarboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid; α,β-ethylenically unsaturated polycarboxylic acids such as itaconic acid, maleic acid, and fumaric acid; and α,β-ethylenically unsaturated polycarboxylic acid partial esters such as monomethyl itaconate, monobutyl maleate, and monopropyl fumarate. In addition, those having a group that can be derived into a carboxylic acid group by hydrolysis, such as maleic anhydride and itaconic anhydride, can also be used. Among these, itaconic acid, acrylic acid, and methacrylic acid are preferred, and acrylic acid is more preferred, from the viewpoints of reactivity with the crosslinking agent described below, stability of the polymer latex, and cost. The unsaturated carboxylic acid monomers may be used alone or in combination of two or more kinds.

[0028] The proportion of the unsaturated carboxylic acid monomer unit in the polymer is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, more preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 2.5% by mass or less, based on 100% by mass of all repeating units (all monomer units) contained in the polymer. When the proportion of the unsaturated carboxylic acid monomer unit in the polymer is 0.1% by mass or more, the crosslinking reaction by the crosslinking agent described later can be sufficiently promoted. As a result, the resin residue on the adherend of the self-adhesive laminate having the foam sheet can be suppressed while imparting sufficient strength to the foam sheet. On the other hand, when the proportion of the unsaturated carboxylic acid monomer unit in the polymer is 10% by mass or less, it becomes easy to keep the viscosity of the polymerization system during polymerization within an appropriate range, and the self-adhesive force of the foam sheet is not impaired due to excessive crosslinking of the polymer.

[0029] The vinyl cyanide monomer unit is a repeating unit derived from a vinyl cyanide monomer. A specific example of the vinyl cyanide monomer is an α,β-ethylenically unsaturated nitrile monomer. The α,β-ethylenically unsaturated nitrile monomer is not particularly limited as long as it is an α,β-ethylenically unsaturated compound having a nitrile group, and examples thereof include acrylonitrile; α-halogenoacrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; and α-alkylacrylonitrile such as methacrylonitrile and α-ethylacrylonitrile. Among these, acrylonitrile is preferred from the viewpoint of increasing the breaking strength of the foamed sheet. The vinyl cyanide monomers may be used alone or in combination of two or more.

[0030] The proportion of the vinyl cyanide monomer unit in the polymer is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 15% by mass or less, based on 100% by mass of all repeating units (all monomer units) contained in the polymer. If the proportion of the vinyl cyanide monomer unit in the polymer is 1% by mass or more, the foam sheet can be given sufficient strength while suppressing the resin residue on the adherend of the self-adhesive laminate having the foam sheet. On the other hand, if the proportion of the vinyl cyanide monomer unit in the polymer is 30% by mass or less, the flexibility of the foam sheet can be sufficiently secured, and a self-adhesive laminate having good self-adhesive strength can be obtained.

[0031] An alkenyl aromatic monomer unit is a repeat unit derived from an alkenyl aromatic monomer. Specific examples of alkenyl aromatic monomers include styrene, α-methylstyrene, α-chlorostyrene, vinyltoluene, divinylbenzene, etc. Among these, styrene is preferred from the viewpoints of polymerizability and cost. The alkenyl aromatic monomers may be used alone or in combination of two or more kinds.

[0032] The proportion of the alkenyl aromatic monomer unit in the polymer is preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 1.5% by mass or more, and preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on the total repeating units (total monomer units) contained in the polymer being 100% by mass. If the proportion of the alkenyl aromatic monomer unit in the polymer is 0.5% by mass or more, the hydrophobicity of the alkenyl aromatic monomer unit can prevent water from penetrating into the foamed sheet, and the water resistance of the foamed sheet can be improved. On the other hand, if the proportion of the alkenyl aromatic monomer unit in the polymer is 20% by mass or less, the flexibility of the foamed sheet can be sufficiently ensured, and a self-adhesive laminate having good self-adhesive strength can be obtained.

[0033] The other monomer units are repeating units derived from other monomers copolymerizable with the above-mentioned monomers. Examples of the other monomers include conjugated diene monomers, α,β-ethylenically unsaturated polyvalent carboxylic acid complete ester monomers, carboxylic acid unsaturated alcohol ester monomers, olefin monomers, crosslinkable monomers, etc. These monomers may be used alone or in combination of two or more.

[0034] Specific examples of the conjugated diene monomer include butadiene, isoprene, 1,3-pentadiene, and cyclopentadiene.

[0035] Specific examples of the α,β-ethylenically unsaturated polyvalent carboxylic acid complete ester monomer include dimethyl fumarate, diethyl fumarate, dimethyl maleate, diethyl maleate, and dimethyl itaconate.

[0036] Specific examples of the carboxylic acid unsaturated alcohol ester monomer include vinyl acetate.

[0037] Specific examples of the olefin monomer include ethylene, propylene, butene, and pentene.

[0038] The crosslinkable monomer is a monomer capable of efficiently crosslinking the inside of a polymer molecule and / or between polymer molecules. The crosslinkable monomer is not particularly limited as long as it can crosslink a polymer, and examples of the crosslinkable monomer include a polyfunctional monomer having a plurality of polymerizable unsaturated bonds (excluding the above-mentioned conjugated diene monomer) and a monomer having a crosslinkable functional group.

[0039] When a crosslinkable monomer is used, the proportion of the crosslinkable monomer units in the polymer is preferably 0.1% by mass or more and 10% by mass or less, with the total repeating units (total monomer units) contained in the polymer being 100% by mass. If the proportion of the crosslinkable monomer units in the polymer is within the above range, it becomes easy to keep the viscosity of the polymerization system during polymerization within an appropriate range, and it becomes easy to prevent the self-adhesiveness of the foamed sheet from being impaired due to excessive crosslinking of the polymer.

[0040] As the polyfunctional monomer, for example, a bifunctional monomer such as divinylbenzene, ethylene diacrylate, ethylene dimethacrylate, allyl methacrylate, etc.; a trifunctional monomer such as trimethylolpropane trimethacrylate, etc. can be used. The polyfunctional monomer preferably has an unsaturated bond at the end. The polyfunctional monomer may be used alone or in combination of two or more kinds.

[0041] Examples of the monomer having a crosslinkable functional group include monomers having a functional group such as an organic acid group other than a carboxy group, a hydroxyl group, an amino group, an amide group, a mercapto group, or an epoxy group.

[0042] The monomer having an organic acid group is not particularly limited, but a representative example thereof is a monomer having an organic acid group such as a sulfonic acid group. In addition, a monomer having a sulfenic acid group, a sulfinic acid group, a phosphoric acid group, or the like can also be used.

[0043] Specific examples of the monomer having a sulfonic acid group include α,β-unsaturated sulfonic acids such as allylsulfonic acid, methallylsulfonic acid, vinylsulfonic acid, and acrylamido-2-methylpropanesulfonic acid, and salts thereof.

[0044] When the monomer having an organic acid group is used, the content of the monomer unit derived from the monomer having an organic acid group in the polymer is preferably 0.1% by mass to 10% by mass, more preferably 0.5% by mass to 5% by mass. When the content of the monomer unit derived from the monomer having an organic acid group in the polymer is within the above range, it becomes easy to keep the viscosity of the polymerization system during polymerization within an appropriate range, and it becomes easy to prevent the self-adhesiveness of the foamed sheet from being impaired due to excessive crosslinking of the polymer.

[0045] Incidentally, it is simple and preferable to introduce the monomer unit having an organic acid group into the polymer by polymerization of a monomer having an organic acid group, but the organic acid group may be introduced by a known polymer reaction after the polymer is produced.

[0046] When a monomer having a functional group other than an organic acid group (hydroxyl group, amino group, amide group, epoxy group) is used, the content of monomer units derived from the monomer having the functional group other than the organic acid group in the polymer is preferably 10% by mass or less. When the content of monomer units derived from the monomer having the functional group other than the organic acid group in the polymer is 10% by mass or less, it becomes easy to keep the viscosity of the polymerization system during polymerization within an appropriate range, and it becomes easy to prevent the self-adhesiveness of the foamed sheet from being impaired due to excessive crosslinking of the polymer.

[0047] In order to sufficiently suppress the generation of formaldehyde during the formation of a foamed sheet, the polymer preferably does not have an N-methylol group. More specifically, the polymer preferably does not contain a monomer unit having an N-methylol group. Here, examples of the monomer having an N-methylol group include N-methylol acrylamide and N-methylol methacrylamide.

[0048] The polymer preferably has the following properties:

[0049] Specifically, the glass transition temperature of the polymer is preferably -10°C or lower, more preferably -13°C or lower, even more preferably -17°C or lower, and particularly preferably -20°C or lower. If the glass transition temperature of the polymer is -10°C or lower, the self-adhesive strength of the foamed sheet is sufficiently ensured while the self-adhesive laminate including the foamed sheet can be well adhered to the adherend. This makes it possible to prevent moisture from penetrating between the adherend and the foamed sheet. Therefore, the water resistance of the self-adhesive laminate including the foamed sheet can be increased. The lower limit of the glass transition temperature of the polymer is not particularly limited, but is preferably −40° C. or higher from the viewpoint of sufficiently suppressing the resin residue on the adherend of the self-adhesive laminate having a foam sheet. The glass transition temperature of the polymer can be obtained, for example, by measuring the glass transition temperature of a film obtained by drying a polymer latex containing the polymer using a differential scanning calorimeter in accordance with JIS K 7121. As the differential scanning calorimeter, for example, DSC7000X (manufactured by Hitachi High-Tech Science Corporation) can be used.

[0050] The gel fraction of the polymer is preferably 95% by mass or less, more preferably 93% by mass or less. If the gel fraction is 95% by mass or less, a foamed sheet having appropriate self-adhesive strength and excellent smoothness can be obtained. The lower limit of the gel fraction of the polymer is not particularly limited, but can be, for example, 50% by mass or more, and can be 70% by mass or more. The gel fraction of the polymer can be measured, for example, by the following method. First, the polymer is applied onto a 50 μm-thick polyethylene terephthalate (PET) film with a 250 μm applicator, and dried at room temperature for 24 hours to obtain a resin film. A predetermined amount (X) (about 500 mg) of this film is precisely weighed as a sample, and this is immersed in 100 mL of ethyl acetate at room temperature for 3 days, and then the insoluble matter is filtered through a 200-mesh wire net, air-dried at room temperature for 15 hours, then dried at 100° C. for 2 hours, cooled at room temperature, and the weight (Y) of the sample is measured. Then, the gel fraction is calculated by substituting X and Y into the following formula. Gel fraction (%) = (Y) / (X) x 100

[0051] The polymerization method for obtaining the above-mentioned polymer is not particularly limited, and may be any of solution polymerization, emulsion polymerization, suspension polymerization, bulk polymerization, etc., or other methods. There is no particular limit to the type or amount of polymerization initiator, emulsifier, dispersant, etc. used in the polymerization. There is no particular limit to the method of adding monomer, polymerization initiator, emulsifier, dispersant, etc. during polymerization. There is also no particular limit to the polymerization temperature, pressure, stirring conditions, etc.

[0052] [Metal oxide cellulose nanofiber] Metal-containing oxidized cellulose nanofibers that contain a metal other than sodium in the form of a salt are components that impart deodorizing properties to the foam sheet. The metal-containing oxidized cellulose nanofibers are not particularly limited as long as they have deodorizing properties. Furthermore, the metal-containing oxidized cellulose nanofibers can impart strength to the foam sheet. Therefore, the foam sheet can be made low density while maintaining its strength. By making the foam sheet low density (i.e., by forming more bubbles in the foam sheet), the contact area between the metal-containing oxidized cellulose nanofibers and the outside air increases, improving the deodorizing power of the foam sheet. Therefore, by including the metal-containing oxidized cellulose nanofibers, the deodorizing properties of the foam sheet can be improved while maintaining its strength.

[0053] Here, the metal other than sodium contained in the metal-containing oxidized cellulose nanofibers can be a metal depending on the properties to be imparted to the metal-containing oxidized cellulose nanofibers. From the viewpoint of deodorizing properties, the metal other than sodium can be, for example, at least one metal selected from the metals of Groups 2 to 14 and Periods 3 to 6 of the Long Periodic Table; more preferably at least one selected from the group consisting of magnesium, aluminum, calcium, titanium, chromium, manganese, iron, cobalt, nickel, copper, zinc, silver, tin, barium, and lead; even more preferably at least one selected from the group consisting of aluminum, calcium, iron, cobalt, copper, zinc, and silver; and particularly preferably at least one selected from the group consisting of silver, zinc, and copper. Metal-containing oxidized cellulose nanofibers containing copper and silver (copper-containing oxidized cellulose nanofibers, silver-containing oxidized cellulose nanofibers) are particularly excellent in deodorizing the odor of sulfur-based malodorous gases such as hydrogen sulfide and methyl mercaptan.

[0054] The amount of metal other than sodium in the metal-containing oxidized cellulose nanofibers is not limited as long as the desired properties can be imparted to the resulting foam sheet. For example, in the above-mentioned metal-containing carboxylated cellulose nanofibers, the metal other than sodium is preferably present in a ratio of 1 / 3 or more, more preferably 1 / 2 or more, of the molar amount of carboxy groups in the carboxylated cellulose nanofibers. The greater the content of the metal other than sodium in the metal-containing oxidized cellulose nanofibers, the more the deodorizing properties of the resulting foam sheet can be improved.

[0055] The metals in the metal-containing oxidized cellulose nanofibers can be qualitatively and quantitatively determined by ICP-AES according to the method described in, for example, JP 2016-141777 A or JP 2019-199622 A.

[0056] The metal-containing oxidized cellulose nanofibers are preferably metal-containing carboxylated cellulose nanofibers, because metal-containing carboxylated cellulose nanofibers have excellent dispersibility and can impart desired properties such as deodorizing properties to the foam sheet even when incorporated in a small amount.

[0057] Here, the carboxylated cellulose nanofibers constituting the above-mentioned metal-containing carboxylated cellulose nanofibers are those in which the primary hydroxyl groups at the 6-positions of the β-glucose units of the raw cellulose have been oxidized to carboxy groups via aldehyde groups. From the viewpoint of imparting sufficient desired properties to the metal-containing carboxylated cellulose nanofibers, it is preferred that the primary hydroxyl groups in the carboxylated cellulose nanofibers are oxidized to carboxy groups by preferably 50 mol % or more, more preferably 70 mol % or more, and even more preferably 90 mol % or more.

[0058] The amount of carboxy groups in the metal-containing carboxylated cellulose nanofibers can be measured according to the method described in JP-A-2016-141777 or JP-A-2019-199622.

[0059] The metal-containing oxidized cellulose nanofiber preferably has the following properties:

[0060] Specifically, the number average fiber diameter of the metal-containing oxidized cellulose nanofibers is preferably 100 nm or less, more preferably 50 nm or less, even more preferably 30 nm or less, and particularly preferably 10 nm or less, because metal-containing oxidized cellulose nanofibers having a number average fiber diameter of 100 nm or less have excellent dispersibility and can satisfactorily impart desired properties such as deodorizing properties to the foamed sheet even when incorporated in a small amount.

[0061] The number average fiber length of the metal-containing oxidized cellulose nanofibers is preferably 50 nm or more and 2000 nm or less, more preferably 70 nm or more and 1500 nm or less, even more preferably 100 nm or more and 1000 nm or less, and particularly preferably 400 nm or more and 600 nm or less. If the number average fiber length is 50 nm or more, the foamed sheet can be imparted with sufficiently high mechanical strength. If the number average fiber length is 2000 nm or less, the dispersibility of the metal-containing oxidized cellulose nanofibers can be ensured.

[0062] The number average fiber length of the metal-containing oxidized cellulose nanofibers can be adjusted, for example, by changing the number average fiber length of the natural cellulose used as the raw material, the oxidation treatment conditions, and the conditions for dispersing (defibrating) the carboxylated cellulose nanofibers after the oxidation treatment. Specifically, the number average fiber length can be shortened by extending the time of the dispersion treatment (defibration treatment).

[0063] The number-average fiber length of the metal-containing oxidized cellulose nanofibers can be measured, for example, by measuring the fiber lengths of five or more metal-containing oxidized cellulose nanofibers using an atomic force microscope and calculating the average of the obtained measured values. As the atomic force microscope, for example, a Dimension FastScan AFM (manufactured by BRUKER, Tapping mode) can be used.

[0064] Furthermore, the metal-containing oxidized cellulose nanofibers preferably have an average degree of polymerization (the average number of glucose units contained in a cellulose molecule) of 100 or more and 2000 or less, more preferably 300 or more and 1500 or less, even more preferably 500 or more and 1000 or less, and particularly preferably 500 or more and 700 or less. When the average degree of polymerization is 100 or more, the foamed sheet can be imparted with sufficiently high mechanical strength. When the average degree of polymerization is 2000 or less, the dispersibility of the metal-containing oxidized cellulose nanofibers can be ensured.

[0065] The average degree of polymerization of the metal-containing oxidized cellulose nanofibers can be adjusted by changing the average degree of polymerization of the natural cellulose used as the raw material, the oxidation treatment conditions, and the conditions for dispersing (defibrating) the carboxylated cellulose nanofibers after the oxidation treatment.

[0066] The average degree of polymerization of metal-containing oxidized cellulose nanofibers can be determined, for example, by the method described in "Isogai, A., Mutoh, N., Onabe, F., Usuda, M., "Viscosity measurements of cellulose / SO 2- The measurement can be performed in accordance with the method described in "Sen'i Gakkaishi, 45, 299-306 (1989)."

[0067] Furthermore, the above-mentioned metal-containing oxidized cellulose nanofibers containing metals other than sodium in the form of salts can be produced, for example, according to the methods described in JP-A-2016-141777 and JP-A-2019-199622. The metal-containing oxidized cellulose nanofibers containing a metal other than sodium in the form of a salt produced as described above are usually obtained as a dispersion in a dispersion medium such as water.

[0068] Furthermore, from the viewpoint of achieving both adsorptivity and deodorizing properties at an even higher level in the foam sheet, the content of the metal-containing oxidized cellulose nanofiber in the foam sheet is preferably 0.1 part by mass or more, more preferably 0.3 part by mass or more, and even more preferably 0.4 part by mass or more, and is preferably 1.0 part by mass or less, more preferably 0.9 part by mass or less, and even more preferably 0.8 part by mass or less, relative to 100 parts by mass of the polymer.

[0069] [Other additives] The foam sheet may optionally contain various additives to improve the processability during the preparation process of the foam sheet and to improve the performance of the foam sheet. Examples of such additives include crosslinking agents, foam stabilizers such as higher fatty acid salts and surfactants, foaming assistants, thickeners, fillers, preservatives, fungicides, gelling agents, flame retardants, antioxidants, antioxidants, pigments, dyes, tackifiers, conductive compounds, water-resistant agents, and oil-resistant agents. Specific examples of the other additives described above are not particularly limited, and known additives, such as those described in International Publication No. 2016 / 147679, can be used.

[0070] Here, the crosslinking agent is not particularly limited as long as it can form a crosslinked structure with the above-mentioned polymer (particularly the unsaturated carboxylic acid monomer unit of the above-mentioned polymer). Examples of such crosslinking agents include carbodiimide-based crosslinking agents; epoxy-based crosslinking agents; oxazoline-based crosslinking agents; polyfunctional isocyanate-based crosslinking agents such as tolylene diisocyanate, trimethylolpropane tolylene diisocyanate, and diphenylmethane triisocyanate; metal salt-based crosslinking agents; metal chelate-based crosslinking agents; and peroxide-based crosslinking agents. Among them, epoxy-based crosslinking agents are preferably used, and compounds having two or more epoxy groups in one molecule are more preferably used. As the epoxy-based crosslinking agent, fatty acid polyglycidyl ether, glycerol polyglycidyl ether, and ethylene glycol diglycidyl ether are preferred.

[0071] Here, the epoxy-based crosslinking agent may be synthesized by a known method, or a commercially available product may be used. An example of a commercially available epoxy-based crosslinking agent is "Rikabond (registered trademark)" manufactured by Japan Coating Resin Co., Ltd. The epoxy-based crosslinking agent forms a crosslinked structure within or between the molecules of the polymer by reacting the epoxy group contained therein with a functional group in the polymer (e.g., a carboxylic acid group derived from an unsaturated carboxylic acid monomer unit). By using the epoxy-based crosslinking agent, a foamed sheet having a suitable self-adhesive strength and excellent strength can be formed. Therefore, by using the epoxy-based crosslinking agent as the crosslinking agent, the resin residue on the adherend of the foamed sheet can be suppressed.

[0072] In the present invention, it is preferable not to use a crosslinking agent that generates formaldehyde, such as a melamine-formaldehyde resin, a urea-formaldehyde resin, or a phenol-formaldehyde resin.

[0073] Here, the amount of the crosslinking agent is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 3 parts by mass or more, and preferably 20 parts by mass or less, more preferably 10 parts by mass or less, per 100 parts by mass of the above-mentioned polymer. By using the amount of the crosslinking agent within the above-mentioned range, a foamed sheet with appropriate strength and elasticity can be obtained. Therefore, when the pressure applied to the foamed sheet is released, the foam cells in the foamed sheet that have been crushed can recover to their original shape. In addition, the self-adhesive force of the foamed sheet can be ensured, and the resin residue on the adherend of the foamed sheet can be sufficiently suppressed.

[0074] As the foam stabilizer, fatty acid ammonium such as ammonium stearate; sulfonic acid type anionic surfactants such as alkyl sulfosuccinate; quaternary alkyl ammonium chloride; alkyl betaine amphoteric compounds; and fatty acid alkanolamines can be used.

[0075] Further, as the thickener, acrylic polymers such as sodium polyacrylate, inorganic compound fine particles such as fine silica, and reactive inorganic compounds such as magnesium oxide can be used.

[0076] [Properties of foam sheet] The self-adhesive foam sheet preferably has the following properties:

[0077] The density of the foamed sheet is not particularly limited, but is preferably 0.3 g / cm 3 It is preferable that the content is 0.4 g / cm or more. 3 More preferably, it is 0.7 g / cm or more. 3 It is preferable that the concentration is 0.6 g / cm or less. 3 It is more preferable that the density of the foamed sheet is 0.3 g / cm or less. 3 If the density of the foamed sheet is 0.7 g / cm or more, the strength of the foamed sheet can be ensured. 3 If the content is equal to or less than this, the deodorizing properties of the foam sheet can be ensured while the air release properties (the ability to easily remove air trapped between the foam sheet and the adherend) can be sufficiently increased.

[0078] The thickness of the foam sheet is preferably 30 μm or more, more preferably 50 μm or more, and even more preferably 100 μm or more, and is preferably 3 mm or less, more preferably 1 mm or less, even more preferably 500 μm or less, and particularly preferably 400 μm or less. If the thickness of the foam sheet is 30 μm or more, the deodorizing property and mechanical strength of the foam sheet can be sufficiently ensured. On the other hand, if the thickness of the foam sheet is 3 mm or less, a self-adhesive laminate having excellent repetitive attachment properties (rework performance) can be obtained.

[0079] The foam sheet preferably contains open cells formed by a plurality of bubbles communicating with each other. If the foam sheet contains such open cells, the air trapped between the foam sheet and the adherend can be easily removed to the outside of the foam sheet through the open cells, so that the air release property of the foam sheet is further improved, and the foam sheet can be attached to the adherend neatly and easily. If the foam sheet contains such open cells, the contact area with the outside air is increased, so that more odorous components can be deodorized, so that the deodorizing property of the foam sheet is further improved. From the viewpoint of further improving the air release property and the deodorizing property, the open cells in the foam sheet preferably contain open cells extending in the planar direction of the foam sheet. The open cells in the foamed sheet can usually be confirmed by observing a cross section of the foamed sheet using, for example, a laser microscope, a digital microscope, a scanning electron microscope or the like.

[0080] <Base material> The base material has a permeability of 0 cm 3 / cm 2 / sec and has a basis weight of 40 g / m 2 Any base material may be used as long as it satisfies the above requirements.

[0081] Among them, as the substrate, it is preferable to use fiber substrates such as woven fabric, nonwoven fabric, paper, etc. And, from the viewpoint of achieving both the deodorizing property and strength of the self-adhesive laminate at a high level, as the fiber substrate, it is preferable to use natural fibers such as cotton, silk, pulp, etc.; polyamide synthetic fibers; polyester synthetic fibers; polypropylene synthetic fibers; polyvinyl chloride synthetic fibers; polyvinyl alcohol synthetic fibers; semi-synthetic fibers such as acetate; regenerated artificial fibers such as rayon; and sheet-like substrates made of mixtures or laminates of these fibers, and from the viewpoint of improving heat resistance, it is more preferable to use sheet-like substrates containing PET fibers, and more preferable to use nonwoven fabrics containing PET fibers.

[0082] Here, from the viewpoint of further enhancing the deodorizing properties of the self-adhesive laminate, the air permeability of the substrate is 15 cm 3 / cm 2 / sec or more is preferable, and 30 cm 3 / cm 2 / sec or more is preferable, and 50 cm 3 / cm 2 More preferably, the air permeability of the substrate is 800 cm 3 / cm 2 / sec or less.

[0083] In order to prevent the material used to form the foam sheet from penetrating the substrate, the basis weight of the substrate is 45 g / m 2 From the viewpoint of facilitating the permeation of gases containing odorous substances and enhancing the deodorizing properties of the self-adhesive laminate, the basis weight of the substrate is preferably 90 g / m 2 It is preferable that the thickness is less than 60 g / m 2 It is more preferable that:

[0084] From the viewpoint of achieving a high level of both improved deodorizing properties of the self-adhesive laminate and suppression of permeation of the material used to form the foam sheet, the thickness of the substrate is preferably 10 μm or more, more preferably 130 μm or more, and even more preferably 150 μm or more, and is preferably 500 μm or less, and more preferably 350 μm or less. If both the basis weight and thickness of the substrate are within the above ranges, the tensile strength of the substrate can be increased.

[0085] (Method of manufacturing self-adhesive laminate) The method for producing the self-adhesive laminate of the present invention includes a step of foaming a composition for a self-adhesive foam sheet to obtain a foamed composition (foaming step), and a step of forming the foamed composition into a sheet on a substrate (sheet forming step). The laminate obtained through the above-mentioned steps is not particularly limited, but for example, a separator film may be attached to the self-adhesive surface (i.e., the surface on the foamed sheet side), and then the laminate may be wound up by a winder and cut to an easy-to-use size by press cutting, a slitter, or the like.

[0086] <Foaming process> In the foaming step, a composition for a self-adhesive foam sheet (hereinafter, sometimes referred to as a "composition for a foam sheet") is foamed to obtain a foam composition.

[0087] [Self-adhesive foam sheet composition] Here, the foam sheet composition contains a polymer and metal-containing oxidized cellulose nanofibers that contain a metal other than sodium in the form of a salt, and optionally further contains a solvent and other additives.

[0088] The polymer, metal-containing oxidized cellulose nanofiber containing a metal other than sodium in the form of a salt, and other additives that can be contained in the foam sheet composition can be the same as those described above for the self-adhesive foam sheet of the self-adhesive laminate of the present invention. The preferred forms and blending ratios of these can also be the same as those described above for the self-adhesive foam sheet of the self-adhesive laminate of the present invention.

[0089] Although the polymer can be used in the form of a solid in the preparation of the foam sheet composition, it is preferable to use the polymer in the form of a latex containing the polymer (polymer latex), such as a latex obtained by emulsion polymerization or a latex obtained by post-emulsification of the polymer, in the preparation of the foam sheet composition, because this allows for easy operation in mixing the polymer with oxidized cellulose nanofibers containing a metal other than sodium in the form of a salt, any solvents that are used, and other additives, and is also convenient for foaming the obtained foam sheet composition. When the polymer is used in the form of a polymer latex for preparing a foam sheet composition, the solids concentration of the polymer latex is preferably 40% by mass or more, more preferably 45% by mass or more, even more preferably 50% by mass or more, particularly preferably 52% by mass or more, from the viewpoint of maintaining the density of the resulting foam sheet, and is preferably 70% by mass or less, and more preferably 58% by mass or less.

[0090] The metal-containing oxidized cellulose nanofibers can be used in the preparation of a foam sheet composition in the form of a dispersion in a dispersion medium such as water, in which the metal-containing oxidized cellulose nanofibers are highly dispersed, preferably to a level such that the number average fiber diameter is 100 nm or less, more preferably 2 to 50 nm, even more preferably 2 to 10 nm, and particularly preferably 2 to 5 nm. Therefore, by using this dispersion, a composition for foam sheets that can provide a foam sheet with excellent deodorizing effect can be obtained. Specifically, by adding the dispersion containing the metal-containing oxidized cellulose nanofibers as it is to the above-mentioned polymer or polymer latex and stirring the resulting mixture, a composition for foam sheets in which the metal-containing oxidized cellulose nanofibers are sufficiently dispersed can be obtained. Furthermore, it is preferable to add the dispersion containing the metal-containing oxidized cellulose nanofibers little by little to the stirred polymer or polymer latex using a pipette or the like, since this prevents aggregation of the metal-containing oxidized cellulose nanofibers. Here, the solids concentration of the metal-containing cellulose nanofibers in the dispersion is preferably 0.1% or more and 2.0% or less. If the solids concentration is 0.1% or more, it is possible to prevent the content of the dispersion medium such as water in the obtained foam sheet composition from increasing, which would cause a decrease in the viscosity of the composition, and to form a smoother and more uniform sheet. On the other hand, if the solids concentration is 2.0% or less, it is possible to prevent the dispersion from becoming pseudo-gelled like a jelly, and it is possible to further improve the dispersibility of the metal-containing cellulose nanofibers in the obtained foam sheet composition. When using solid metal-containing oxidized cellulose nanofibers, the above dispersion may be dried by a known method.

[0091] The solvent that may be optionally contained in the composition for foam sheets is not particularly limited, but water is preferred. When water is used as the solvent, the water contained in the composition for foam sheets may be, for example, water derived from a polymer latex and / or water derived from an aqueous dispersion of metal-containing oxidized cellulose nanofibers that contain metals other than sodium in the form of salts. The water contained in the composition for foam sheets may also be water derived from other additives.

[0092] When the foam sheet composition contains a solvent (taking the form of a dispersion in which metal-containing oxidized cellulose nanofibers are dispersed), the viscosity of the foam sheet composition is preferably 800 mPa·s to 10,000 mPa·s, more preferably 900 mPa·s to 8,000 mPa·s, and even more preferably 1,000 mPa·s to 7,500 mPa·s. If the foam sheet composition has a viscosity of 800 mPa·s or more, it is possible to prevent dripping, which makes it difficult to control the thickness, when the foam sheet is formed by applying the foam composition formed from the foam sheet composition to a substrate. On the other hand, if the foam sheet composition has a viscosity of 10,000 mPa·s or less, it is also possible to prevent difficulty in controlling the expansion ratio by mechanical foaming when forming a foam sheet. The viscosity of the foam sheet composition can be measured at 23° C. using a Brookfield viscometer.

[0093] The pH of the foam sheet composition is preferably 5 or more, more preferably 7 or more, and even more preferably 8 or more, and is preferably 10 or less, more preferably 9.7 or less, and even more preferably 9.5 or less. When the pH of the foam sheet composition is 5 or more, it is possible to effectively prevent the precipitation and aggregation of nanofibers caused by the metal of the metal-containing cellulose nanofiber containing a metal other than sodium in the form of a salt being removed to form a carboxylic acid, and the sedimentation caused by the aggregation of the removed metal ions. On the other hand, when a crosslinking agent is used, the pH of the foam sheet composition is 10 or less, it is possible to effectively prevent a decrease in the strength of the foam sheet caused by the crosslinking reaction being less likely to proceed. The pH of the composition for a foam sheet can be measured at a temperature of 23° C. using a pH meter.

[0094] The foam sheet composition can be produced by mixing the metal-containing oxidized cellulose nanofibers containing a polymer and a metal other than sodium in the form of a salt with a solvent and other additives that are used as desired, by any method.

[0095] For example, when a polymer latex is used in preparing a foam sheet composition, metal-containing oxidized cellulose nanofibers containing a metal other than sodium in the form of a salt and other optional additives may be added to the polymer latex and mixed by a known method.

[0096] Furthermore, for example, when a dispersion of metal-containing oxidized cellulose nanofibers containing a metal other than sodium in the form of a salt is used in preparing a foam sheet composition, a solid polymer or polymer latex and other optional additives may be added to this dispersion and mixed by a known method.

[0097] Furthermore, for example, when a solvent is not used in preparing a foam sheet composition, a solid polymer, a metal-containing oxidized cellulose nanofiber containing a metal other than sodium in the form of a salt, and other solid additives that are optionally used may be mixed by a known method, for example, using a known roll, Henschel mixer, kneader, or the like.

[0098] From the viewpoint of favorably dispersing metal-containing oxidized cellulose nanofibers containing a metal other than sodium in the form of a salt in the foam sheet composition, it is preferable to add a dispersion (e.g., an aqueous dispersion) of metal-containing oxidized cellulose nanofibers containing a metal other than sodium in the form of a salt to the polymer latex under stirring to obtain a mixed liquid, and then optionally add other additives to the mixed liquid and further mix by a known method. It is preferable that other additives that increase the viscosity in the system, such as crosslinking agents and thickeners, are added as late as possible to maintain a uniform composition in the system.

[0099] [Foam] Mechanical foaming is usually used as a method for foaming the composition for foamed sheets. The foaming ratio may be adjusted as appropriate, but is usually 1.2 to 5 times, preferably 1.5 to 4 times. The mechanical foaming method is not particularly limited, but can be performed by mixing a certain amount of air into the dispersion of the composition for foamed sheets and stirring it continuously or batchwise with an oak mixer, whipper, or the like. The foamed dispersion thus obtained is creamy. By forming pores by the mechanical foaming, a foamed sheet having excellent air escape properties can be finally obtained. When the foaming ratio is 1.2 times or more, the air escape properties can be prevented from decreasing, and when the foamed sheet is 5 times or less, the strength can be prevented from decreasing.

[0100] <Sheet making process> In the sheet forming step, the foaming composition obtained in the foaming step is formed into a sheet on a substrate, and the sheet-shaped foaming composition is solidified as necessary to form a foamed sheet on the substrate.

[0101] [Base material] Here, the base material is a material with an air permeability of 0 cm 3 / cm 2 / sec and the basis weight is 40 g / m 2 A substrate having an air permeability of 0 cm or more is used. Specifically, the substrate may be the same as the substrate described above with respect to the self-adhesive laminate of the present invention. 3 / cm 2 If a substrate having a basis weight of more than 40 g / m2 is used, the deodorizing properties of the resulting self-adhesive laminate can be improved. 2 As long as this is the case, even if a breathable substrate is used, the foaming composition can be prevented from penetrating the substrate, thereby preventing contamination of the manufacturing equipment and reduced yield caused by the foaming composition, while also ensuring sufficient tensile strength of the substrate.

[0102] [Sheet] The method of forming the foaming composition into a sheet on the substrate is not particularly limited. A suitable method is, for example, a method of applying the foaming composition to the substrate in a sheet form. As a method of applying the foaming composition to the substrate, for example, a method using a commonly known coating device such as a roll coater, a reverse roll coater, a screen coater, a doctor knife coater, or a comma knife coater can be used.

[0103] The solidification of the foaming composition, which is carried out as necessary, is carried out, for example, by crosslinking the polymer of the foaming composition in the form of a sheet. The method of crosslinking the polymer is not limited, but a method of heating and drying the foaming composition is preferred. The method of heating and drying is not particularly limited as long as it is a method that can dry the foaming composition on the substrate or the like and crosslink the polymer, and a known drying oven (for example, a hot air circulation type oven, a hot oil circulation hot air chamber, a far infrared heater chamber) can be used. The drying temperature can be, for example, 60°C or higher and 180°C or lower. In addition, it is preferable to perform multi-stage drying such that drying is performed from the inside at a low temperature in the early stage of drying and is sufficiently dried at a higher temperature in the later stage of drying, rather than performing drying at a constant temperature.

[0104] In this manner, a self-adhesive laminate is obtained which comprises a self-adhesive foam sheet formed by solidifying the sheet-like foam composition on a substrate or the like.

[0105] (Applications of laminates) The substrate surface of the self-adhesive laminate of the present invention can be printed by, for example, offset printing, seal printing, flexographic printing, silk screen printing, gravure printing, laser printers, thermal transfer printers, inkjet printers, or the like. Laminated sheets with printing on the base surface can be advantageously used for outdoor applications such as sales promotion cards, so-called POP cards (posters, stickers, displays, etc.), gardening POP (insert labels, etc.), road signs (for funerals, home exhibitions, etc.), and signboards (no entry, forest road work, etc.), as well as indoor applications such as being attached to wallpaper, flooring, and wall materials. EXAMPLES

[0106] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In addition, in a polymer produced by polymerizing a plurality of types of monomers, the ratio of a monomer unit formed by polymerizing a certain monomer in the polymer usually coincides with the ratio (feed ratio) of the certain monomer to the total monomers used in the polymerization of the polymer, unless otherwise specified. Various measurements and evaluations in the examples and comparative examples were performed according to the following methods.

[0107] <Thickness of substrate> Eight pieces of the substrate were cut into a square of 50 mm×50 mm, and the arithmetic mean value of the thicknesses measured using a thickness meter (PEACOK MODEL H, manufactured by Ozaki Seisakusho) was taken as the thickness of the substrate. <Base material weight> For eight substrates cut into 50 mm x 50 mm squares, the basis weight (= {arithmetic mean value of weight / (50 mm x 50 mm)}) was calculated from the arithmetic mean value of the weight measured using a balance (BM-252, manufactured by A&D Co., Ltd.). <Breathability of the base material> The measurements were performed using a Frazier type tester according to JIS L1913 and the Frazier type method. <Coatability of foam composition> After the production of the laminate, the surface of the automatic coater was visually observed, and the coatability was evaluated according to the following criteria. A: The foaming composition does not pass through the substrate, and no stains are observed on the surface of the automatic coater. B: The foaming composition passes through the substrate, and stains are observed on the surface of the automatic coater. <Deodorizing properties of self-adhesive laminate> The laminate thus produced was cut to a size of 100 mm x 100 mm x thickness, and the foamed sheet side was attached to a soda glass of 120 mm x 120 mm x 1 mm to obtain a sample. The sample was placed in a sampling pack (GL Sciences, SMART BAG PA AA-5), and the opening was heat-sealed to seal. The sampling pack was degassed using a vacuum pump, and 3 L of a gas of a predetermined concentration (hydrogen sulfide gas: 80 ppm by mass) was sealed in the sampling pack. After that, the gas concentration (ppm by mass) in the pack was measured using a gas detector tube (Gastec, gas detector tube) at a predetermined time. The shorter the gas concentration is reduced, the better the deodorizing properties are.

[0108] Example 1 <Preparation of polymer latex> A monomer mixture consisting of 64 parts by mass of ethyl acrylate, 12 parts by mass of 2-ethylhexyl acrylate, 12 parts by mass of n-butyl acrylate, 9 parts by mass of acrylonitrile, 2 parts by mass of styrene, and 1 part by mass of acrylic acid, and 0.4 parts by mass of sodium polyoxyethylene alkyl sulfate (manufactured by Kao Corporation, Latemul E-118B) were mixed and stirred into 27.0 parts by mass of deionized water to obtain a monomer emulsion. Next, a glass reaction vessel equipped with a reflux condenser, a dropping funnel, a thermometer, a nitrogen inlet, and a stirrer was prepared separately from the above, and 43.0 parts by mass of deionized water and 0.2 parts by mass of sodium polyoxyethylene alkyl sulfate were placed in this glass reaction vessel, and the temperature was raised to 80°C while stirring. Then, while maintaining the temperature at 80°C, 0.3 parts by mass of ammonium persulfate dissolved in 5.7 parts by mass of deionized water was added, and then the monomer emulsion obtained above was gradually added over 4 hours. After the addition was completed, stirring was continued for another 4 hours, and then the reaction was terminated by cooling to obtain a reaction mixture. The polymerization conversion rate at this time was 98% or more, and the resulting reaction mixture was adjusted to pH 5.0 with 5% by mass ammonia water, and 2.5 parts by mass of polyoxyethylene lauryl ether (manufactured by Kao Corporation, Emulgen 120) was added, followed by concentration to obtain a polymer latex with a solid content concentration of 58% by mass. <Preparation of copper-containing TEMPO-oxidized cellulose nanofiber aqueous dispersion> 1 g of bleached softwood kraft pulp (dry weight equivalent), 5 mmol of sodium hypochlorite, 0.1 g (1 mmol) of sodium bromide, and 0.016 g (1 mmol) of TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl) were dispersed in 100 mL of water, gently stirred at room temperature for 4 hours, and washed with distilled water to obtain TEMPO-catalyzed oxidized pulp (oxidized cellulose). The amount of carboxyl groups in the obtained TEMPO-catalyzed oxidized pulp was 1.4 mmol / g. Then, distilled water was added to the undried TEMPO-catalyzed oxidized pulp to prepare an aqueous dispersion with a solid content of 0.1%. The aqueous dispersion was then defibrated using a homogenizer (Microtec Nithion, Hiscotron) at 7.5×1000 rpm for 2 minutes, and an ultrasonic homogenizer (Nissei, Ultrasonic Generator) for 4 minutes with V-LEVEL4, TIP26D while cooling the container with ice to obtain an aqueous dispersion containing TEMPO carboxylated cellulose nanofibers as TEMPO-oxidized cellulose nanofibers. The undefibrated components were then removed from the aqueous dispersion of TEMPO carboxylated cellulose nanofibers by centrifugation (12000G (120×100 rpm / g), 10 minutes, 12℃) using a centrifuge (SAKUMA, M201-1VD, angle rotor 50F-8AL) to obtain an aqueous dispersion of TEMPO carboxylated cellulose nanofibers with a solid content of 0.1% by mass, which was a transparent liquid. In addition, the TEMPO carboxylated cellulose nanofiber contained sodium derived from the co-oxidant in the form of a salt. Next, 1 mL of 1 M hydrochloric acid was added to 100 mL of the TEMPO carboxylated cellulose nanofiber aqueous dispersion under stirring to adjust the pH to 1. Stirring was then continued for 60 minutes. Thereafter, the TEMPO carboxylated cellulose nanofibers that had been gelled by the addition of hydrochloric acid were collected by centrifugation (12,000 G), and the collected TEMPO carboxylated cellulose nanofibers were washed successively with 1 M hydrochloric acid and a large amount of distilled water. Next, 100 mL of distilled water was added to obtain a hydrogen-substituted TEMPO carboxylated cellulose nanofiber aqueous dispersion with a concentration of 0.1% by mass. The carboxy groups on the surface of the hydrogen-substituted TEMPO carboxylated cellulose nanofiber were measured by FT-IR (JASCO Corporation, FT / IR-6100) according to Biomacromolecules (2011, Vol. 12, pp. 518-522) and found to be substituted with carboxylic acid groups at least 90%. Then, 50 g of the above-mentioned 0.1% by mass hydrogen-substituted TEMPO carboxylated cellulose nanofiber aqueous dispersion was stirred, and 18 g of a 0.1% by mass copper acetate aqueous solution was added thereto, and stirring was continued for 3 hours at room temperature. After that, the carboxylated cellulose nanofiber gelled by the addition of the copper acetate aqueous solution was collected by centrifugation (12000G (120×100 rpm / g), 10 minutes, 12° C.) using a centrifuge (SAKUMA, M201-1VD, angle rotor 50F-8AL), and the collected cellulose nanofiber was washed with a 0.1% by mass copper acetate aqueous solution, and then the collected cellulose nanofiber was washed with a large amount of distilled water. Then, 50 mL of distilled water was added, and an ultrasonic homogenizer (Nissei, Ultrasonic Generator) was used to perform ultrasonic treatment (2 minutes) with V-LEVEL4, TIP26D while cooling the container with ice to disperse the copper-substituted TEMPO carboxylated cellulose nanofibers. Then, the copper-substituted TEMPO carboxylated cellulose nanofiber aqueous dispersion was centrifuged (12000G (120×100 rpm / g), 10 minutes, 12° C.) using a centrifuge (SAKUMA, M201-1VD, angle rotor 50F-8AL). As a result, an aqueous dispersion of copper-containing TEMPO oxidized cellulose nanofibers (hereinafter, simply referred to as “TOCN-Cu”) with a solid content concentration of 0.1% by mass was obtained. Then, this aqueous dispersion was concentrated using an evaporator to obtain an aqueous dispersion of TOCN-Cu with a solid content concentration of 0.94% by mass. <Preparation of Foam Composition> 300 g of the polymer latex (solid concentration 58% by mass) was weighed out into a 500 mL disposable cup and stirred (1750 rpm) with a mixer (Tokushu Kika Kogyo, ROBOMICS). 18.62 g of the TOCN-Cu aqueous dispersion (solid concentration: 0.94% by mass) (TOCN-Cu content: 0.1 parts by mass relative to 100 parts by mass of polymer) was gradually added in small portions to the stirred polymer latex, and stirring was continued for 30 minutes after the addition. Thereafter, while stirring the resulting mixture, 12 g of ammonium stearate (manufactured by San Nopco, Nopco DC-100A, concentration: 30% by mass) as a foam stabilizer, 9 g of fatty acid polyglycidyl ether (manufactured by Japan Coating Resins, Rikabond EX-8, concentration: 100% by mass) as an epoxy crosslinking agent, and 9 g of sodium polyacrylate (manufactured by Toagosei, Aron A-20L, concentration: 15% by mass) as a thickener were added to the mixture in that order, and then stirred for 30 minutes to obtain a foam sheet composition. The solid content of the foam sheet composition was 54% by mass, the viscosity measured at 23°C using a B-type viscometer (manufactured by Rion, "VISCOTESTER VT-06") was 4300 mPa·s, and the pH measured at 23°C using a pH meter (manufactured by HORIBA, pH METER F-52) was 8.69. The composition for foamed sheets was foamed using a whisk (Tescom Co., Ltd., hand mixer THM272) to a foaming ratio of 2 times and a density of 0.49 g / cm 3 A foaming composition (foaming liquid) of the above formula was obtained. <Preparation of self-adhesive laminate> The foaming liquid prepared above was applied to the substrate (PET nonwoven fabric) shown in Table 1 using an automatic coater (main body: TQC Sheen, AFA-Standard KT-AB4420, applicator: Cortec, Multi-applicator MA-250). The PET nonwoven fabric to which the foaming liquid was applied was placed in an 80°C oven (Yamato Scientific, DNF400) for 80 seconds, then in a 120°C oven (Yamato Scientific, DNF400) for 120 seconds, and finally in a 140°C oven (Yamato Scientific, DNF400) for 120 seconds to dry, forming a foamed layer (thickness: 120 μm, density: 0.43 g / cm) made of a foam sheet on the substrate. 3 ) was obtained. The coating properties and deodorizing properties were then evaluated, and the results are shown in Table 1.

[0109] (Examples 2 to 6) A laminate was produced and evaluated in the same manner as in Example 1, except that the substrate (PET nonwoven fabric) shown in Table 1 was used as the substrate. The results are shown in Table 1.

[0110] (Comparative Examples 1 to 2) When an attempt was made to prepare a laminate in the same manner as in Example 1, except that the substrate (PET nonwoven fabric) shown in Table 1 was used as the substrate, the foaming liquid passed through the substrate, and the desired foamed sheet could not be formed. Therefore, the deodorizing property was not evaluated.

[0111] (Comparative Examples 3 to 4) Laminates were produced and evaluated in the same manner as in Example 1, except that the substrates shown in Table 1 (synthetic paper or PET film) were used. The results are shown in Table 1.

[0112] [Table 1]

[0113] From Table 1, it is seen that the laminates of Examples 1 to 6 are excellent in deodorizing properties and can be efficiently manufactured. Among them, it is seen that the laminates of Examples 1 and 2 are particularly excellent in deodorizing properties. Furthermore, from Table 1, it is seen that in Comparative Examples 1 and 2, which use a substrate with a small basis weight, the laminates cannot be efficiently manufactured. Furthermore, from Table 1, it is seen that in Comparative Examples 3 and 4, which use a substrate with no breathability, the deodorizing properties cannot be sufficiently improved. [Industrial Applicability]

[0114] According to the present invention, it is possible to provide a self-adhesive laminate which has excellent deodorizing properties and can be efficiently produced.

Claims

1. A self-adhesive laminate comprising a substrate and a self-adhesive foam sheet, The self-adhesive foam sheet comprises a polymer including a (meth)acrylate monomer unit and a metal-containing oxidized cellulose nanofiber including a metal other than sodium in the form of a salt, the metal other than sodium is at least one selected from the group consisting of silver, zinc, and copper; The substrate has an air permeability of 4 cm 3 / cm 2 / sec or more and 800 cm 3 / cm 2 / sec or less, and the basis weight is 45 g / m 2 or more and 90 g / m 2 or less.

2. The self-adhesive laminate according to claim 1 , wherein the number average fiber diameter of the metal-containing oxidized cellulose nanofibers is 100 nm or less.

3. The self-adhesive laminate according to claim 1 or 2, wherein the metal-containing oxidized cellulose nanofibers are metal-containing carboxylated cellulose nanofibers.

4. The self-adhesive laminate according to any one of claims 1 to 3, wherein the substrate contains PET fibers.

5. A step of foaming a composition for a self-adhesive foam sheet, the composition including a polymer including a (meth)acrylate monomer unit and a metal-containing oxidized cellulose nanofiber including a metal other than sodium in the form of a salt, to obtain a foam composition; forming the foam composition into a sheet on a substrate; Including, the metal other than sodium is at least one selected from the group consisting of silver, zinc, and copper; The substrate has an air permeability of 4 cm 3 / cm 2 / sec or more and 800 cm 3 / cm 2 / sec or less, and the basis weight is 45 g / m 2 The method for producing a self-adhesive laminate according to any one of claims 1 to 4, wherein the weight of the self-adhesive laminate is from 0.01 to 90 g / m 2 .

Citation Information

Patent Citations

  • Resin composition, self-adsorption foamed sheet and protective material

    JP2006176693A

  • Wall covering decorative sheet raw material and wall covering decorative sheet

    JP2006306072A

  • Method for manufacturing foamed wallpaper

    JP2013053391A

  • Resin composition for self-sticking foamed sheet, self-sticking foamed sheet, and self-sticking foamed laminated sheet

    JP2016172805A

  • Cleaning sheet and method for manufacturing the same

    JP2018172802A